Strategi Promosi Perpustakaan dalam Meningkatkan Jumlah Kunjungan Pemustaka di Perpustakaan Daerah Deli Serdang - Suryani, Nani; Sayekti, Retno; Faturrahman, Muslih (ARZUSIN, 2024)
The purpose of this research is to find out how librarian tactics encourage library use and increase interest in visits. in the Deli Serdang regional library, to find out the causes of the low interest in visiting public libraries in Deli Serdang and the challenges of librarians in encouraging public library patronage in Deli Serdang Regency. This type of research combines field study methodology with qualitative research. Librarian The research topic is the Deli Serdang Regency Public Library. There are three techniques used to obtain data: observation, interviews, and documentation. Data presentation, data reduction procedures, and data analysis methods were all carried out in accordance with descriptive analysis. Based on the research results, the author can determine librarian tactics to encourage increased interest in visiting libraries in the Deli Serdang regional library, including by conducting mobile library activities, holding reading competitions for the community. Furthermore, knowing the lack of library collections, facilities and infrastructure, as well as inadequate library services is one of the factors causing the low interest in visiting public libraries in Deli Serdang. Librarians also face challenges in efforts to increase interest in visiting the Deli Serdang Regency public library.